Delivery methods and outcomes of eHealth programmes in neonatal transitional care for families of preterm or medically complex infants: a scoping review protocol - Laura Rasero; Emanuele Buccione; Camilla Elena Magi; Stefano Bambi (BMJ Open)
Introduction The transition from the neonatal intensive care unit (NICU) to home is a critical period for families with preterm or medically complex infants and is often marked by stress, anxiety and the challenge of managing complex medical regimens. Virtual programmes such as mobile health applications and telehealth interventions have emerged as promising tools to support families during this transition. These programmes aim to provide continuous education and support after discharge. This scoping review will map the existing evidence on virtual interventions supporting families during the NICU-to-home transition and identify their delivery methods and reported outcomes.Methods and analysis This protocol outlines a scoping review methodology, as described by Arksey and O’Malley and further improved by Levac et al. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Review will be used as a guiding framework for scoping reviews. A comprehensive search will be conducted in six databases: PubMed, Scopus, Web of Science, Embase, CINAHL and PsycINFO. Studies will be included if they (1) focus on virtual programmes supporting families of preterm or medically complex infants, (2) involve transitional care during discharge from the NICU to home and (3) are primary studies. Grey literature, as well as secondary and tertiary literature will be excluded. Data will be charted and analysed to summarise the delivery methods, target populations and outcomes reported.Ethics and dissemination No ethical approval is required for this study. The findings will be disseminated through publications in peer-reviewed journals and presentations to the relevant stakeholders.Trial registration number This scoping review protocol is registered in the Open Science Framework (https://doi.org/10.17605/OSF.IO/HWVZJ).